The short-term and long-term trade-off between risk and return: chaos vs rationality - Liu, Chang; Shi, Haoming; Wu, Liang; Guo, Min (Journal of Business Economics and Management, 2020)
This paper used the composite construction method proposed by Haugen (1999) and its application by Zhao and Wang (2010) for the Chinese stock market. Utilizing the Shanghai A-share market stocks data, this paper first selected the shares listed on the Shanghai Stock Exchange during January 1, 1997 to December 31, 2017. A portfolio was then built according to the mean variance model of portfolio structure, and simulation results were analysed using the Wilcoxon Signed Rank Test. The relationship between risk and return in the long and short term was explored. Results indicated no significant relationship between the risk and return of the stock portfolio in the short run, which reflects the complexity of the Chinese stock market. However, in the long run, the risk and return of the stock portfolios are positively correlated, which means that high returns are accompanied by high risks, indicating that the stock market will eventually return to rationality. In other words, the A-share stock market will eventually return to be value-driven and the short-term speculators would be outweighed by long-term value investors. First published online 07 November 2019